When Value Meets Trust: Exploring the Impact of Electronic Word of Mouth on Customer Loyalty - Tri Ari Mukti; Rindika Pramadanti (Universitas Proklamasi 45, 2026)
This study explores how perceived value and trust shape electronic word of mouth and customer loyalty in the hospitality industry, positioning e-WOM as an intervening variable. A quantitative research design was employed, with primary data collected via questionnaires distributed to 157 guests of the Grand Zuri Jababeka Hotel in November 2025, using purposive sampling. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that both perceived value and trust significantly and positively influence e-WOM and customer loyalty. Moreover, e-WOM plays a significant role in driving customer loyalty and acts as a partial mediator in the relationships between perceived value and customer loyalty, and between trust and customer loyalty. These findings underscore the strategic importance of strengthening perceived value and trust to stimulate favorable e-WOM and enhance long-term customer loyalty. The study offers managerial implications for hotel practitioners aiming to improve service performance and develop more effective marketing initiatives.